A Complex Condition; Polycystic Ovary Syndrome (PCOS): A Review of its Recent Advanced Treatment - Wal, Pranay; Saxena, Bhagawati; Aziz, Namra; Pyne, Chandana; Wal, Ankita; Rathore, Shruti (Current Women's Health Reviews, 2024)
Polycystic ovary syndrome (PCOS) is a common endocrine and metabolic disorder affecting women worldwide. It refers to a condition that often has ‘poly’ liquid containing sacks around ovaries. It affects reproductive-aged females, giving rise to menstrual and related reproductive issues. PCOS is marked by hormonal imbalance, often resulting in hyperandrogenism. Women with PCOS might experience abnormal insulin activity and complications such as acne, mood swings, hirsutism, obesity, and infertility. The disease is linked with severe clinical ailments such as type 2 diabetes (T2DM), cardiovascular diseases (CVDs), and cancer. A faulty lifestyle, neuroendocrine factors, genetic causes, and androgen exposures often cause PCOS. The approach of society towards physiological problems such as PCOS in women is that it must be under the veil that is the ultimate barrier to the early diagnosis of PCOS. Thus, this review summarizes the causes, symptoms, pathophysiology, diagnosis, and possible treatment (medical, herbal, and lifestyle improvement, acupuncture, and bariatric surgery) related to PCOS.
Keywords: infertility